PREDICTIVE ROLE OF INFARCT RELATED ARTERY IN ACUTE RIGHT VENTRICULAR INFARCTION DIAGNOSED USING ELECTROCARDIOGRAPHY - Andova, Valentina; Zafirovska, Planinka; Papestiev, Vasil; Georgievska-Ismail, Ljubica (Journal of Morphological Sciences; Vol 5 No 3 (2022): JMS, 2022)
Right coronary artery (RCA) emerged as infarct related artery (IRA) in patients with right ventricular myocardial infarction (RVMI), which is followed by some degree of RV dysfunction. The aim of our study was to identify significant predictors of IRA among angiographic and/or echocardiographic data of RV dimension and/or function in patients with acute RVMI. Out of 122 hospitalized patients with acute inferior myocardial infarction, on the basis of ECG criteria RVMI was diagnosed in 58/47.5% patients. Coronary angiography was applied in 52/89,6% immediately after admission and conventional 2D echocardiography was performed in all referred patients in order to assess right heart dimensions and function according to the professional association recommendations. RCA emerged as IRA in 49/84,5 % of patients with echocardiographicaly diagnosed RVMI. Patients with RCA stenosis/occlusion had 4.9 times higher risk for RVMI presence (OR=4.941; 95%CI: 1.727-14.136; p=0.003) than those without and had significantly worse echocardiographic assessed RV global and/or regional systolic function. Logistic stepwise regression analysis confirmed the significant role of  enlarged RV dimension (OR=1.1; 95%CI: 1.023-1.182; p=0.010), RCA stenosis/occlusion presence (OR=4.8; 95%CI: 1.649-14.199; p=0.004) and/or LAD stenosis/occlusion absence (OR=0.18; 95%CI: 0.067-0.476; p=0.001) in prediction of RVMI. The optimal sensitivity of the model was 90% and specificity 75%. RCA and conversely lack of LAD stenosis/occlusion presence along with some of the echocardiographic parameters showing RV dysfunction increased the odds for RVMI. Applying immediate and complete reperfusion of RCA is of a great importance for recovery of RV function. Key words: right myocardial infarction, right coronary artery, right ventricular dysfunction, reperfusion.